Factors influencing intention of lodging service entrepreneurs to run sharia lodging service business - Aulia, Almas Jilan; Wiliasih, Ranti (IPB University, 2024)
Sembungan Village is a predominant Muslim community that won the Pioneer Tourism Village Category at the 2022 Indonesia Tourism Village Award. The strong community backing offers great opportunities for developing halal tourism in the village. Therefore, this study aimed to analyze the factors influencing intention of lodging business actors to operate their business based on Sharia principles in Sembungan Village. By using multiple regression analysis of data from 35 business actors, religiosity and attitudes toward behavior were identified as the main factors influencing intention. The results showed the importance of strengthening religious values and encouraging positive attitudes in promoting and developing Sharia lodging in tourism village.